ANALISIS KEANEKARAGAMAN GEN MYOSTATIN (MSTN) SECARA IN-SILICO PADA CATTLE DI INDONESIA - Naufal Ma'arif; Hanum Isfaeni; Asep Gunawan (Bioma, 2023)
Cattle is one of the largest livestock products in Indonesia. The purpose of this study was to determine the diversity of the myostatin (MSTN) gene found in several cattle in Indonesia. This research was a descriptive analysis research based on several literature studies. Gene data was taken from the National Center for Biotechnology Information (NCBI). The gene data taken were from several species such as Bos indicus, Bos indicus×Bos taurus, and Bos taurus. Meanwhile, Bubalus bubalis, Capra hircus, and Cervis sp. were selected as outgroups. DNA sequence data analysis was aligned using MEGA XI software. MSTN gene parameters showed results between the kinship of several cattle in Indonesia. From these results it can be found that there were still several species of cattle in Indonesia that were not yet found in the NCBI database on the MSTN gene. For example, Madura cattle (Bos javanicus), PO Kebumen, PO Aceh, and several livestock products that do not yet have the MSTN gene characterization database. Therefore, to improve the quality of beef in Indonesia, it is necessary to characterize the MSTN gene in several species that are not yet in the database as a benchmark for the quality level of cattle in Indonesia.